Desperately Seeking a Communicative Approach: English Pronunciation in a Sample of French and Polish Secondary School Textbooks - Henderson, Alice; Jarosz, Anna (Research in Language, 2014)
This paper compares the treatment of English pronunciation in school textbooks from France and Poland, in order to see what resources teachers have at their disposal. It is limited to textbooks used at the secondary level of each education system. Recent research has shown that European teachers do not find teaching English pronunciation easy and that many are unsatisfied with their training in relation to teaching pronunciation (Bradford & Kenworthy 1991; Burgess and Spencer 2000; Henderson et al. 2012; Frost and Henderson, 2013; Iivonen, 2005). Textbooks are a widespread resource with the potential to alleviate a lack of extensive pedagogical training. The first part of this paper analyses pronunciation exercises in a representative sample of textbooks from each country. Pronunciation exercises were classified based on the degree to which they mobilize communicative abilities, according to the five categories of a Communicative Framework for teaching pronunciation (Celce-Murcia et al., 2010, p45): Description & analysis, Listening discrimination, Controlled practice, Guided practice, Communicative practice. The first category involves little risk-taking by the learner, usually focusses on form and allows little freedom. At the other end of the spectrum, communicative practice involves a focus on meaning and interaction, with the concomitant greater freedom to make mistakes. The exercises were then analysed to see which segmental and/or prosodic features they favoured and to what extent.